2014
DOI: 10.1038/bjc.2014.278
|View full text |Cite
|
Sign up to set email alerts
|

TBLR1 is a novel prognostic marker and promotes epithelial–mesenchymal transition in cervical cancer

Abstract: Background:Invasion and metastasis remain a critical issue in cervical cancer. However, the underlying mechanism of it in cervical cancer remains unclear. The newly discovered protein, TBLR1, plays a crucial role in regulating various key cellular functions.Methods:In this study, western blot, real-time RT–PCR, immunohistochemical staining, 3D morphogenesis Matrigel culture, wound healing and Boyden chamber invasion assays, xenografted tumour model, luciferase assays, and chromatin immunoprecipitation assays w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 50 publications
1
56
0
Order By: Relevance
“…It reduces the expression of β-catenin (epithelial marker) and increases the expression of Vim1 and fibronectin (mesenchymal markers). It increases the invasive properties of cervical cancer cells and further activates the NF-kB and Wnt/bcatenin pathways to regulate the expressions of SNAI1 and Twist in cervical cancer [88].…”
Section: Role Of Other Proteins and Emt In Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…It reduces the expression of β-catenin (epithelial marker) and increases the expression of Vim1 and fibronectin (mesenchymal markers). It increases the invasive properties of cervical cancer cells and further activates the NF-kB and Wnt/bcatenin pathways to regulate the expressions of SNAI1 and Twist in cervical cancer [88].…”
Section: Role Of Other Proteins and Emt In Cervical Cancermentioning
confidence: 99%
“…TBLR1 plays a role in the induction of EMT and is associated with pelvic lymph node metastasis and prognosis in stage Ia2-IIa2 in cervical cancer patients. TBLR1 is of great clinical value as a potential early biomarker to improve the diagnosis and prognostic assessment of cervical cancer patients [88]. Sam68 causes lymph node metastasis in cervical cancer patients by inducing EMT.…”
Section: Impact Of Emt In Clinical Treatment Of Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…TBLR1 is overexpressed in several types of cancer and functions as an oncogene by activation of important intracellular signaling pathways including the Wnt-β-catenin pathway and the nuclear factor-kappa (NF-kB) pathway [11, 24]. TBLR1 expression has a positive correlation with disease progression, tumor metastasis, and drug resistance [1618, 25–27]. Our previous study has shown that TBLR1 is a transcriptional activator of AR and its nuclear expression is significantly reduced in PCa compared with benign prostate glands.…”
Section: Discussionmentioning
confidence: 99%
“…TBLR1 is also a strong coactivator of AR in prostate cancer, leading to selective activation of growth suppressive AR target genes and tumor suppression. In contrast to the reduced expression of TBLR1 in PCa, expression of TBLR1 is upregulated in breast, colon, esophageal squamous cell and nasopharyngeal carcinomas (NPC) and is a potential prognostic marker for aggressive cervical cancer [1618]. Overexpression of TBLR1in NPC cells causes reduced sensitivity to cisplatin-induced apoptosis [18].…”
Section: Introductionmentioning
confidence: 99%